Allogeneic hematopoietic stem-cell transplantation for myelofibrosis. (February 2020) - Zhang, Lining; Yang, Fan; Feng, Sizhou
Myelofibrosis is one of the Philadelphia chromosome (Ph)-negative myeloproliferative neoplasms with heterogeneous clinical course. Though many treatment options, including Janus kinase (JAK) inhibitors, have provided clinical benefits and improved survival, allogeneic hematopoietic stem-cell transplantation (AHSCT) remains the only potentially curative therapy. Considering the significant transplant-related morbidity and mortality, it is crucial to decide who to proceed to AHSCT, and when. In this review, we discuss recent updates in patient selection, prior splenectomy, conditioning regimen, donor type, molecular mutation, and other factors affecting AHSCT outcomes. Relapse is a major cause of treatment failure; we also describe recent data on minimal residual disease monitoring and management of relapse. In addition, emerging studies have reported pretransplant therapy with ruxolitinib for myelofibrosis showing favorable results, and further research is needed to explore its use in the post-transplant setting.